Meanings of Public and the Future of Public Services - McDonald, David (Taylor & Francis, 2022)
Critically assessing meanings of the term "public", this book situates the emergence and expansion of "public services" within market-based forms of production and consumption. It highlights the potential for making public services more progressive within market societies, but underscores their ongoing capture by private interests and emphasises the inherent limits of reform within a ""bourgeois public sphere"". The author explores opportunities for more expansive forms of non-marketized public services, examining emerging debates on the theory and practice of equitable, participatory and sustainable forms of publicness that go beyond mere ownership. The book then asks how we can build a robust international ""pro-public"" movement that juggles universal needs with local context. With a focus on essential public services such as water, electricity and health, the text is global in its scope and written for a broad audience. It will be useful for those interested in social and public policy, public services and public administration, political theory, economic geography, social movements, sustainability and development.